Electric Vehicles Charging Management System for Optimal Exploitation of Photovoltaic Energy Sources Considering Vehicle-to-Vehicle Mode - Lo Franco, Francesco; Mandrioli, Riccardo; Ricco, Mattia; Monteiro, Vítor; Monteiro, Luís F. C.; Afonso, João L.; Grandi, Gabriele (Frontiers in Energy Research, 2021)
The growing penetration of distributed renewable energy sources (RES) together with the increasing number of new electric vehicle (EV) model registrations are playing a significant role in zero-carbon energy communities' development. However, the ever-larger share of intermittent renewable power plants, combined with the high and non-modulable aggregate-EV charging demand requires an evolution towards new planning and management paradigms of energy districts. Thus, in this context, this paper proposes novel smart charging (SC) techniques that aim to integrate as much as possible RES generation and EV charging demand at the local level, synergically acting on power flows and avoiding detrimental effects on the electrical power system. To make this possible, a centralized charging management system (CMS) capable of individually modulating each charging power of plugged EVs is presented in this paper. The CMS aims to maximize the charging self-consumption from local RES, flattening the peak power required to the external grid. Moreover, the CMS guarantees an overall good state of charge (SOC) at departure time for all the vehicles without requiring additional energy from the grid even under low RES power availability conditions. Two methods that differ as a function of the EV power flow direction are proposed. The first SC only involves unidirectional power flow, while the second one also considers bi-directional power flow among vehicles, operating in vehicle-to-vehicle (V2V) mode. Finally, simulations are presented considering an actual case study validate the SC effects on a reference scenario consisting of an industrial area having a PV plant, non-modulable electrical loads, and EV charging stations. Results are collected and performance improvements by operating the different SC methods are compared and described in detail in this paper.